Resiliensi Ekologi dalam Pengelolaan Zona Merah Pasca Bencana Likuefaksi Balaroa - Akbar Akbar; Muhammad Arsyad; Rifai Mardin; Supriadi Takwin (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2026)
The Balaroa area in Palu City suffered severe damage due to liquefaction caused by the 2018 earthquake. According to Regional Regulation No. 10 of 2019, the area was designated as a red zone, where reconstruction is prohibited. This disaster led to parts of the area being permanently restricted from redevelopment, requiring appropriate management strategies to provide solutions for the affected community. This study aims to formulate an ecological resilience-based management strategy for the red zone in the post-disaster context. Using a descriptive qualitative case study approach, the research involved analyzing the physical environmental conditions, conducting interviews with experts and local residents, and reviewing literature related to ecological resilience and red zone management following the Balaroa liquefaction disaster. The findings show that red zones can be optimized as multifunctional green spaces, including memorial parks, water catchment areas, and disaster education zones. This approach supports not only ecological recovery but also strengthens social interaction within the community. Furthermore, the study identifies the community’s social and economic capacities, risk perceptions, and resilience practices such as disaster preparedness and sustainability. With the right management strategy, red zones can be used productively without violating existing regulations. Post-disaster red zones can serve not only as conservation spaces but also as symbols of resilience and recovery.